The amazing spider-man 2 [videorecording (Blu-Ray + DVD)] - Webb, Marc; Kurtzman, Alex; Orci, Roberto; Pinkner, Jeff; Garfield, Andrew, 1983-; Stone, Emma, 1988-; DeHaan, Dane, 1987-; Field, Sally; Foxx, Jamie; Feore, Colm, 1958-; Giamatti, Paul; Jones, Felicity (Sony Pictures Home Entertainment, 2014)
Spider-Man's conflict has been within himself: the struggle between Peter Parker and the responsibilities of Spider-Man, but Peter Parker finds that his greatest battle is about to begin. Peter must confront a foe far more powerful than he, and with the return of old friend Harry Osborn, Peter comes to realize that all of his enemies have one thing in common: Oscorp.